Interpretive walks: advancing the use of mobile methods in the study of entrepreneurial farm tourism settings. (19th January 2018) - Mackay, Michael; Nelson, Tracy; Perkins, Harvey C.
Abstract: This article draws on the application of interpretive walks in a socio‐geographical study of tourism‐oriented entrepreneurial activity on multi‐generational family farms in New Zealand. We highlight the great potential this method holds for tourism researchers interested in the ways tourist spaces are produced in processes of place‐making. Mobile methods have been a feature of qualitative field research in several disciplines for some time, particularly in cultural geography with its emphasis on human interactions in and with landscapes. The interpretive walk, known also as the walking interview, has been applied mainly in urban neighbourhood, health, transport, and housing research, where it has proven very useful for revealing human connections to place that have been difficult to elicit using stationary face‐to‐face interviews. This article is one of the few that reports on the use of the method in a farm tourism setting. It is also one of few applied studies seeking to understand the local geographies of farm tourism and their connections to the farm site as both family home and place of primary production. The method is characterised as an effective tool for navigating and interpreting the socio‐spatial settings in which new rural tourism ventures emerge, evolve, and are embedded. The approach allows for unexpected encounters with spatial practices and strategies, projects, and objects, behind which lie stories of changing human relationships with the land, economy, and community, and of the exigencies of everyday life that are less readily unearthed using conventional interviews.